DMBT1 functions as pattern-recognition molecule for poly-sulfated and poly-phosphorylated ligands - End, Caroline; Bikker, Floris; Renner, Marcus; Bergmann, Gaby; Lyer, Stefan; Blaich, Stephanie; Hudler, Melanie; Helmke, Burkhard; Gassler, Nikolaus; Autschbach, Frank; Ligtenberg, Antoon J. M.; Benner, Axel; et al. (European Journal of Immunology, 2009)
Deleted in malignant brain tumors 1 (DMBT1) is a secreted glycoprotein displaying a broad bacterial-binding spectrum. Recent functional and genetic studies linked DMBT1 to the suppression of LPS-induced TLR4-mediated NF-κB activation and to the pathogenesis of Crohn's disease. Here, we aimed at unraveling the molecular basis of its function in mucosal protection and of its broad pathogen-binding specificity. We report that DMBT1 directly interacts with dextran sulfate sodium (DSS) and carrageenan, a structurally similar sulfated polysaccharide, which is used as a texturizer and thickener in human dietary products. However, binding of DMBT1 does not reduce the cytotoxic effects of these agents to intestinal epithelial cells in vitro. DSS and carrageenan compete for DMBT1-mediated bacterial aggregation via interaction with its bacterial-recognition motif. Competition and ELISA studies identify poly-sulfated and poly-phosphorylated structures as ligands for this recognition motif, such as heparansulfate, LPS, and lipoteichoic acid. Dose-response studies in Dmbt1-/- and Dmbt1+/+ mice utilizing the DSS-induced colitis model demonstrate a differential response only to low but not to high DSS doses. We propose that DMBT1 functions as pattern-recognition molecule for poly-sulfated and polyphosphorylated ligands providing a molecular basis for its broad bacterial-binding specificity and its inhibitory effects on LPS-induced TLR4-mediated NF-κB activation. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Inflammatory bowel disease; Innate immunity; Mucosal immunity; Pattern recognition; Scavenger receptor cysteine-rich